Monitoring of diversity, abundance, activity period and habitat use of wildlife species around the wildlife corridor that connects the natural world heritage site of Thailand - MANANYA PLA-ARD; NORASET KHIOESREE; BUNYATIPORN KEAWDEE; WIPAVEE HUNGHENG; PATTANAPHON CHATTRAKULDEE; PHANITSUPHA PENGTHONG; JIDAPA THONGBANTHUM; PAANWARIS PAANSRI; KHWANRUTAI CHARASPET; TANAPONE PANGANTA; YUWARAK CHANACHAI; PRATEEP DUENGKAE; DOKRAK MAROD; SUWIMOL UTHAIRASMEE; THARNRAT KAEWKRACHANG; NARIS BHUMPAKPHAN; YONGYUT TRISURAT; WARONG SUKSAVATE; SARAWOOD SUNGKAEW; NANTACHAI PONGPATTANANURAK; PHRUET RACHARAK; DECHA WIWATWITTAYA; WATTANACHAI TASEN; ronglarp sukmasuang (Society for Indonesian Biodiversity, 2021)
Abstract. This study on the monitoring of the diversity and abundance of wildlife around the wildlife corridor area on Highway 304, which passes through Khao Yai and Thap Lan National Parks, was conducted during September 2017 and May 2021 using camera traps to constantly monitor the area. A total of at least 51 wildlife species from 30 families, 14 orders were recorded. The species with the highest abundances were Sambar Deer, Wild Boar, Northern Pig-tailed Macaque, Gaur, Northern Red Muntjac, Siamese Fireback, Malayan Porcupine, Red Junglefowl, etc. The wildlife species recorded include 2 critically endangered species, 3 endangered, 10 vulnerable, 1 near threatened. In this study we also recorded images of a Fishing Cat, which is the first photographically record in this World Heritage Site. The evenness index indicates that the wildlife community in the area is stable. No significant differences in the diversity and abundance of wildlife before or after the corridor construction were seen. The wildlife in the area were active throughout the day. We also found that the highway is the main factor effecting the presence of wildlife. The study results show the importance of this area that the highway passes through. Building wildlife corridors between the two national parks is very important for maintaining the wildlife community as well as continuity. Suggestions from the study include management of human activity in the area including traffic, noise, vehicle speed and living activities in the area that may attract wildlife closer to the community and cause other impacts.